2008
DOI: 10.1504/ijstm.2008.022120
|View full text |Cite
|
Sign up to set email alerts
|

Managing and organising technical and scientific service firms: a taxonomy and an empirical study

Abstract: In the last decade, firms have increasingly relied on external sources of technology to support their innovation process. A number of scholars have investigated several aspects of this phenomenon. Little attention has been paid to those companies that offer Technical and Scientific Services (TSS), although their number is increasing and it seems they have a positive impact on client firms' innovative performance.The purpose of this paper is to adopt a firm-level perspective and analyse the key organisational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…nanopowders) to be sold, licensed out or partnered with the client company, that carries out the remaining tasks of the development process and includes them into its innovative products. These companies provide a service of "Work In Progress (WIP) Innovation" (Chiesa et al, 2005b) and typically operate in the category of nanomaterials; M2. the method adopted by nanotech companies carrying out, for the client firm, a particular process (e.g.…”
Section: The Intensive Analysis: Basic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…nanopowders) to be sold, licensed out or partnered with the client company, that carries out the remaining tasks of the development process and includes them into its innovative products. These companies provide a service of "Work In Progress (WIP) Innovation" (Chiesa et al, 2005b) and typically operate in the category of nanomaterials; M2. the method adopted by nanotech companies carrying out, for the client firm, a particular process (e.g.…”
Section: The Intensive Analysis: Basic Resultsmentioning
confidence: 99%
“…thin film deposition) that requires excellent competencies in a specific scientific domain. These companies provide a service of "Process Activity" (Chiesa et al, 2005b), and usually operate in the nanoprocesses category. M3.…”
Section: The Intensive Analysis: Basic Resultsmentioning
confidence: 99%
“…This kind of service can be applied to several sectors: from banking to real estate, from market research to insurance services. Among KIBS, a more specific subset can be identified, called TSS -Technical and Scientific Services (Abetti, 1989;Howells, 1999;Larsen, 2000;den Hertog and Bilderbeek, 2000;Chiesa and Manzini, 2001;Arora et al, 2001;Chiesa et al, 2008;Chiaroni et al, 2008). According to these authors, TSS are "services which rely upon technical and scientific knowledge and give an output that is, again, technical and scientific knowledge."…”
Section: The Conceptual Context Of the Study: The Kibs And The Tss Wimentioning
confidence: 99%
“…Literature (Windrum and Tomlinson, 1999;Debackere 1999;Chiesa andManzini, 2001, Chiesa et al, 2008) has also suggested several taxonomies in order to identify existing service firms. Moreover, there have been some explorative attempts to study more in depth how these service companies are organized and managed by assuming a sort of internal perspective and analyzing the main companies' choices in terms of business model elements (Hargadon and Sutton, 1997;Kelly, 2001;Chiesa et al, 2004;Chiesa et al, 2008), for example in terms of organizational structure (i.e. firm organization, human resources management, level of internal competencies, services offered); commercialisation strategy and marketing approach (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of service can be applied to several sectors: from banking to real estate, from market research to insurance services. Among KIBS, a more specific subset can be identified, called TSSTechnical and Scientific Services (Abetti, 1989;MacPherson, 1997a;MacPherson, 1997b;Howells, 1999;Larsen, 2000;Chiesa & Manzini, 2001;Arora et al, 2001;Chiesa et al, 2008;Chiaroni et al, 2008). According to these authors, TSS are "services which rely upon technical and scientific knowledge and give an output that is, again, technical and scientific knowledge."…”
Section: Introductionmentioning
confidence: 99%